Message From the Symposium Chairs: Isssr 2022 - Wong, W. Eric; Tuğlular, Tuğkan; Wotawa, Franz; Zheng, Liwei; Tuğlular, Tuğkan (IEEE, 2022)
Security, safety, and reliability are the three most important attributes of a system. This is especially the case for mission-critical and life-threatening systems. As the complexity of many systems continues to grow, ensuring security, safety, and reliability has become very critical. Not only does existing technology and tool support need to be enhanced, but we also need new strategies and approaches to satisfy more strict requirements on system security, safety, and reliability. In response to this challenge, the Steering Committee of ISSSR has decided to change its conference name from International Symposium on System and Software Reliability to International Symposium on System Security, Safety, and Reliability. The acronym ISSSR is still the same, but the full name has been slightly modified to emphasize the importance of security, safety, and reliability of many systems.
Keywords: ISSSR 2022